Prognostic value of CRP–albumin–lymphocyte index in patients with intrahepatic cholangiocarcinoma after radical resection - Lang, Shi-Qian; Kong, Jun-Jie; Li, Guang-Bing; Liu, Jun (Frontiers in Medicine, 2025)
PurposeThe aim of this study is to explore the prognostic value of CRP–Albumin–Lymphocyte (CALLY) index in patients undergoing radical resection of intrahepatic cholangiocarcinoma (ICC).Patients and methodsRetrospectively collected clinical data of 286 patients with ICC who underwent radical surgery at Shandong Provincial Hospital from July 2010 to July 2021. Univariate and multivariate analyses were used to evaluate the correlation between the CALLY index and overall survival (OS) and recurrence-free survival (RFS), and a nomogram prediction model was established based on the results. The accuracy of the model was evaluated using concordance index (C-index), calibration curves, decision curve analysis (DCA), and the receiver operating characteristic (ROC) curve was used to compare the prognostic value of the nomogram model with the TNM staging system.ResultsThe optimal cut-off value of CALLY index was 1.81. In the training set, multifactorial Cox regression analysis showed that CALLY index <1.81 was an independent risk factor for OS and RFS (p < 0.05). Compared to neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune inflammation index (SII), and modified Glasgow prognostic score (mGPS), CALLY index had a higher area under the curve (AUC). The nomogram established based on the results of multifactorial analysis demonstrated strong efficacy in survival prediction, and the ROC curve showed that the nomogram had a higher prognostic value than TNM staging.ConclusionThe CALLY index is independently associated with OS and RFS in patients after radical resection of ICC, and the nomogram model based on it shows significantly higher efficacy in predicting the long-term prognosis of patients after radical resection of ICC, and is more accurate than TNM staging.